2015
DOI: 10.1158/2326-6066.cir-14-0180
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of CD169+ Lymph Node Sinus Macrophages in Patients with Malignant Melanoma

Abstract: These data suggest that IFNa-stimulated CD169 þ macrophages inRLNs are closely involved in T-cell-mediated antitumor immunity and may be a useful marker for assessing the clinical prognosis and monitoring antitumor immunity in patients with malignant melanoma.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
81
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(96 citation statements)
references
References 26 publications
9
81
0
Order By: Relevance
“…19 Similar observations were subsequently observed in patients with melanoma, endometrial cancer, and breast cancer. [25][26][27][28] A number of methods for targeting antigens to LN macrophages have been investigated as part of the ongoing development of lymphatic-targeted vaccines. It was reported that cholesteryl pullulan (CHP) nanogels induce tumor regression in some patients with malignant tumors, 29,30 and CD169-positive macrophages in LN sinus captured CHP nanogels and worked as APCs.…”
Section: Discussionmentioning
confidence: 99%
“…19 Similar observations were subsequently observed in patients with melanoma, endometrial cancer, and breast cancer. [25][26][27][28] A number of methods for targeting antigens to LN macrophages have been investigated as part of the ongoing development of lymphatic-targeted vaccines. It was reported that cholesteryl pullulan (CHP) nanogels induce tumor regression in some patients with malignant tumors, 29,30 and CD169-positive macrophages in LN sinus captured CHP nanogels and worked as APCs.…”
Section: Discussionmentioning
confidence: 99%
“…administration of iPS-ML-IFNa cells could decrease the number of endogenous M2 macrophages. We have recently reported that melanoma-bearing patients, especially those with recurrence, have few M1-type macrophages in their regional lymph nodes (19). It therefore makes sense to supply melanoma patients with iPS-ML cells that produce type I IFNs (M1 macrophage-like cells).…”
Section: Accumulation and Infiltration Of Ips-ml In Established Tumormentioning
confidence: 99%
“…Consistent with previous reports, CD169 protein was mainly expressed on CD68 C Mf in the LN sinus. 27,35 Interestingly, multi-staining confocal microscopy analysis revealed a certain proportion of CD169 C cells were CD3 C CD8 C T cells (Fig. 1A and S2).…”
Section: Cd169 C Cd8 C T Cells Accumulate In Regional Ln and Decreasementioning
confidence: 96%